Altered serum glyceraldehyde-derived advanced glycation end product (AGE) and soluble AGE receptor levels indicate carbonyl stress in patients with schizophrenia. (23rd April 2015) - Takeda, Mayu; Ohnuma, Tohru; Takeuchi, Masayoshi; Katsuta, Narimasa; Maeshima, Hitoshi; Takebayashi, Yuto; Higa, Motoyuki; Nakamura, Toru; Nishimon, Shohei; Sannohe, Takahiro; Hotta, Yuri; Hanzawa, Ryo; et al.
Highlights: Advanced glycation end product (AGE) is a carbonyl stress marker of schizophrenia. Glycer-AGE and receptors for AGE (sRAGE) were involved in neurotoxic pathology. We compared serum these markers levels between schizophrenia and controls. Glycer-AGEs and sRAGE levels were significantly higher and lower in schizophrenia. The Glycer-AGEs/sRAGE ratio was altered more in schizophrenia. Abstract: Recent cross-sectional and longitudinal studies indicate that measurements of peripheral blood carbonyl stress markers such as the advanced glycation end product (AGE) pentosidine and the reactive carbonyl-detoxifying B6 vitamin pyridoxal could be used as therapeutic biological markers in subpopulations of schizophrenia patients. Glyceraldehyde-derived AGEs (Glycer-AGE) have strong neurotoxicity, and soluble receptors for AGEs (sRAGE) may ameliorate the effects of AGEs. In the present study, we measured Glycer-AGEs and sRAGE levels to determine their potential as diagnostic, therapeutic, or clinical biological markers in patients with schizophrenia. After enrollment of 61 admitted Japanese patients with acute schizophrenia and 39 healthy volunteers, 54 patients were followed up from the acute stage to remission. Serum biomarkers were measured in blood samples taken before breakfast using competitive enzyme-linked immunosorbent assays, and Glycer-AGEs were significantly higher and sRAGE levels were significantly lower in patients with acute schizophrenia than in healthy controls. Glycer-AGEs/sRAGE ratios were also higher in schizophrenia patients and were stable during the clinical course. Furthermore, discriminant analyses confirmed that Glycer-AGEs and Glycer-AGEs/sRAGE ratios are significant diagnostic markers for schizophrenia, and distinguished between patients and healthy controls in 70.0% of cases. However, these markers of carbonyl stress were not correlated with clinical features, including disease severity, or with daily chlorpromazine doses. These data indicate the potential of Glycer-AGEs, RAGEs, and their relative ratios as diagnostic markers for patients with schizophrenia.